The new early maturing spring barley variety ‘Fedos’ - E. G. Filippov; A. A. Dontsova; D. P. Dontsov; R. N. Bragin (Зерновое хозяйство России, 2021)
In recent years, the spring-summer period of the Rostov region is characterized with a lack of moisture supply in the initial period of plant growing and formation of generative organs, as well as in the filling period of spring barley grain. The highest productivity under these conditions, according to the study of previous years, has been formed by the middle-early and early-maturing varieties. The breeding work for the development of early-maturing spring barley varieties has been going on for many decades in the FSBSI Agricultural Research Center “Donskoy”. The purpose of the current study was to develop a new highly productive early-maturing spring barley variety, adapted to the arid soil and climatic conditions of the south of Russia. The current paper has presented characteristics of the new early-maturing spring barley variety ‘Fedos’, adapted to the soil and climatic conditions of the arid Russian regions and resistant to negative environmental stress factors. The new variety was characterized by high yields (+0.4 t/ha to the standard one), large kernel (1000 kernel weight was more than 47 g), fairly high protein percentage in grain (+1.3% to the standard one). In comparison with the standard variety, the new variety has formed higher yields due to the increased number of productive stems per 1 m2 (on 12 pcs. more) and kernel weight per head (+0.2 g). In addition, the variety ‘Fedos’ produced large, well-filled kernel even in severely arid years (+5.6 g to the standard one). The new variety is more resistant to major leaf diseases than the standard one.